The cost-effectiveness of iruplinalkib versus alectinib in anaplastic lymphoma kinase-positive crizotinib-resistant advanced non-small-cell lung cancer patients in China - Dai, Zhanjing; Xu, Jiayi; Chang, Feng; Zhou, Wanxin; Ren, Ting; Qiu, Jiaxin; Lu, Yun; Lu, Yuqiong (Frontiers in Public Health, 2024)
Background: Iruplinalkib is a second-generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitor (TKI) with efficacy in patients with ALK-positive crizotinibresistant advanced non-small-cell lung cancer (NSCLC), which is independently developed by a Chinese pharmaceutical company. This study examined the costeffectiveness of iruplinalkib versus alectinib in the Chinese healthcare setting. Methods: A partitioned survival model was developed to project the economic and health outcomes. Efficacy was derived using unanchored matching-adjusted indirect comparisons (MAIC). Cost and utility values were obtained from the literature and experts' opinions. Deterministic and probabilistic sensitivity analyses (PSA) were carried out to evaluate the model's robustness. Results: Treatment with iruplinalkib versus alectinib resulted in a gain of 0.843 qualityadjusted life-years (QALYs) with incremental costs of 20,493.27, resulting in an incremental cost-effectiveness ratio (ICER) of 24,313.95/QALY. Parameters related to relative efficacy and drug costs were the main drivers of the model outcomes. From the PSA, iruplinalkib had a 90% probability of being cost-effective at a willingness-topay threshold of 37,863.56/QALY. Conclusions: Compared with alectinib, iruplinalkib is a cost-effective therapy for patients with ALK-positive crizotinib-resistant advanced NSCLC.